The Impact of Maqashid Syariah on the Human Development Index (HDI): The Case of Indonesia - Ahsanul Amal, Muhammad; Gunawan, Dedi; Choiri, Miftakhul; Badrus Zaman, Akhmad Roja (Universitas Muhammadiyah Surakarta, 2024)
This study investigates how the Maqashid al-Shariah framework, encompassing the protection of religion (Hifzu al-Din), life (Hifzu al-Nafs), intellect (Hifzu al-Aql), progeny (Hifzu al-Nasl), and property (Hifzu al-Mal), influences Indonesia's Human Development Index (HDI). This study utilises qualitative research methods and incorporates Eviews-12 software for data analysis, notably using panel data regression techniques with selected Common Effect Model (CEM). The research sample included eight provinces, namely: Papua, West Papua, East Nusa Tenggara, West Sulawesi, West Kalimantan, West Nusa Tenggara, North Maluku, and Gorontalo for the timeframe of 2019-2022. The analysis revealed that protecting religion (Hifzu al-Din) and protecting the mind (Hifzu al-Aql) significantly influence Indonesia's HDI. Interestingly, protecting life (Hifzu al-Nafs), offspring (Hifzu al-Nasl), and property (Hifzu al-Mal) did not show a statistically significant direct impact on HDI in this study. One limitation of the study is the reliance on data from only eight provinces, which may not be representative of the whole territory of Indonesia. The novelty of the research lies in its utilization of the maqashid sharia approach to analyze human development indicators in specific provinces of Indonesia, providing a unique perspective on the factors influencing development in Islamic contexts.